Eye blinking patterns, corneal staining and compliance in a group of soft contact lens wearers - Bashirah Ishak,; Nur Sakinah Saad,; Lim, Siew Lee; Norlaila Mat Daud,; Bariah Mohd Ali,; Norhani Mohidin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Many factors influence the success of contact lens wear, including lens surface moisture, which is affected by blinking. This study was conducted to determine the eye blinking patterns, corneal staining, and compliance in a group of soft contact lens (CL) wearers. Forty-one soft CL wearers and 41 age-matched control subjects (non-CL wearers) were recruited in this study. Blinking patterns were assessed with a digital camera attached to a slit lamp biomicroscope. Corneal staining was graded using Institute for Eye Research (IER) grading scale with 0.1 increments. The subject’s compliance level was determined using a questionnaire. There was no difference in eye blinking patterns between the CL wearers and control group (Mann-Whitney, p = 0.231). The average grades of corneal staining in CL wearers and control group were 0.38 ± 0.39 and 0.01 ± 0.08 unit, respectively. There was a significant difference in corneal staining between the two groups (Mann-Whitney, p = 0.021). A significant positive correlation was found between blinking patterns and corneal staining (Spearman ρ = 0.378, p = 0.015). Our results also showed that 63.4% of the CL wearers had good compliance towards lens care. In our multiple linear regression analysis, blinking patterns contributed significantly to corneal staining (B = 0.140, p = 0.015), while compliance level did not (B = -0.038, p = 0.471). Overall, eye blinking patterns in CL wearers influenced the risk of corneal staining.